Castanea BRA (Blueprint) / Nuramirah Megat Adnan … [et al.]. - Megat Adnan, Nuramirah; Abd Hamid, Hamimah; Iree, Cheryl; Mohamad Khatta, Alya Qistina; Zulkifly, Nur Nashwa; Amran, Nur Ain Humaira (2024)
Brief description of the business and product concepts: Castanea Bra is a form-fitting undergarment that is primarily used to support and cover a woman's breasts. It is developed with a cooling pad technology made out of natural ingredients namely, menthol and camphor as well as using an antimicrobial fabric. The benefits can be experienced as the cooling pads give a cooling sensation to the breasts when worn to minimise discomfort and irritation. The Castanea Bra is suitable for women of all ages, especially for those who live in warm weather in tropical climates. The target market and projections: The Castanea Pte. Ltd. target market is teenagers and adults who experience discomfort during hot weather or when sweating. The reason the company focused on them is because increased body temperature causes the delicate breasts to sweat more. The sweat is frequently trapped by traditional bras, which feeds bacteria and causes irritation. Hence, a cooling pad bra assists the absorption of sweat and the production of a cooling sensation to the breasts. The competitive advantages: The cooling pad bra was inspired by us who experience discomfort when sweating during activity or in hot conditions. Nevertheless, Uniqlo branded bras are very helpful for women in any situation because of the fabric material used. Because of that, to make it different from other brands, the Castanea Pte. Ltd. uses technological cooling pads instead of using technological material clothing.